Hubungan Kadar Kolesterol, Asam Urat dan Gula Darah dengan Kejadian Hipertensi pada Pasien Prolanis Usia 50-75 Tahun di Puskesmas Paron - Putri, Silvia Oktavioni; Waskito, Budi Arief; Soekanto, Ayly (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2025)
Background: The chronic disease service program is designed for all BPJS Kesehatan members who suffer from chronic diseases including type 2 diabetes mellitus and hypertension. Hypertension is diagnosed when a person has systolic blood pressure ≥ 140 mm Hg and/or diastolic blood pressure ≥ 90 mm Hg. Cholesterol, uric acid and blood sugar are triggers for non-communicable diseases, one of which is hypertension. Based on the background above, researchers are interested in conducting a study that aims to determine the relationship between cholesterol, uric acid and blood sugar levels with the incidence of hypertension in Prolanis patients aged 50-75 years at the Paron Health Center, Ngawi Regency in the period January-March 2024. Methods: This study is a cross-sectional study with an observational analysis method using primary data. The population that became the subject of this study were Prolanis hypertension patients aged 50-75 years at the Paron Health Center, Ngawi Regency with a sample taken for this study of 52 patients who had met the inclusion criteria. The data analysis of this study used the chi square test. Results: Based on gender, Prolanis hypertension patients aged 50-75 years in women are 79.5% high cholesterol levels, and male patients are 46.2% high cholesterol levels, in women 56.4% have high uric acid levels and male patients are 53.8% have high uric acid levels, in women 7.7% high blood sugar levels and male patients are 7.7% have high blood sugar levels. Based on obesity status, Prolanis hypertension patients aged 50-75 years who are obese are 89.2% high cholesterol levels and non-obese are 26.7% high cholesterol levels, obese patients are 64.9% high uric acid levels and non-obese patients are 33.3% high uric acid levels, obese patients are 5.4% high blood sugar levels and non-obese patients are 13.3% high blood sugar levels. Conclusion: Based on gender, there is a relationship between cholesterol levels, with the incidence of hypertension in Prolanis patients aged 50-75 years. However, there is no relationship between uric acid levels and blood sugar levels with the incidence of hypertension in Prolanis patients aged 50-75 years. Based on obesity status, there is a relationship between cholesterol and uric acid levels with the incidence of hypertension in Prolanis patients aged 50-75 years. However, there is no relationship between blood sugar levels with the incidence of hypertension in Prolanis patients aged 50-75 years.